“As a husband I will love, lead, and provide”: Gendered access to land in Ghana - Lambrecht, Isabel B. (International Food Policy Research Institute, 2016)
Improving women’s access to land is high on the agricultural policy agenda of both governmental and non-governmental agencies. Yet, the determinants and rationale of gendered access to land are not well understood. This paper argues that gender relations are more than the outcomes of negotiations within households. It explains the importance of social norms, perceptions, and formal and informal rules shaping access to land for male and female farmers at four levels: (1) the household/family, (2) the community, (3) the state, and (4) the market. The framework is applied to Ghana. Norms on household and family organization and on men’s and women’s responsibilities and capabilities play a key role in gendered allocation of resources. However, these norms and perceptions are dynamic and evolve jointly with the development of markets and changes in values of inputs such as labor and land. Theoretical models that represent the gendered distribution of assets as the result of intrahousehold bargaining should be revised, and extrahousehold factors should be included. From a policy perspective, laws that ensure gender equality in terms of inheritance and a more gender-equitable distribution of property upon divorce can play a key role in improving women’s property rights. Yet, their impact may be limited where customary rights dominate and social norms and rules continue to discriminate according to gender.